The Role of Creative Industries in Industrial Innovation - Johannes Trüby; Christian Rammer; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper analyses the role of creative industries in affecting an economy's innovation performance. We conducted a survey of more than 2,000 creative industry enterprises from Austria which are defined by a combination of sector affiliation and the degree of creativity of the services they offer. We show that the creative industries are among the most innovative sectors in the economy. They support innovation in a variety of other sectors through creative inputs, such as ideas for new products (i.e. innovation content), supplementary products and services (such as software) or marketing support for product innovations. What is more, they are also an important user of new technology and demand innovations from technology producers, particularly information and communication technologies. Own innovative activities are a key driver for supporting innovation. Creative industries are no homogenous sector, however. While software and advertising show the strongest links to industrial innovation, architecture and content providers contribute rather little to industrial innovation. A main barrier to fully utilising the innovative potential of this sector is the lack of time at the side of creative entrepreneurs which reflects the small average firm size and the high share of sole traders. Innovation policy in support of creative industries should thus design programmes that are suitable for micro firms.
Keywords: L82; Z1; O31; L86; 330; Creative Industries; Innovation; R&D; Inter-sector Interaction; Innovation Policy; Kreativsektor; Innovation; Forschung; Spillover-Effekt; Österreich